Family Support on Blood Pressure in Elderly Hypertension: A Literature Review - Rahayu, Muthia Ridha; Adriani, Rita Benya; Patriyani, Ros Endah Happy (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: Hypertension is a non-communicable disease that mostly occurs in the elderly and can cause serious complications such as stroke and heart disease. One factor that can help manage hypertension in the elderly is family support. This support plays a role in improving adherence to medication, maintaining a healthy diet, and reducing stress that can affect blood pressure. This study aims to examine the relationship between family support and blood pressure management in hypertensive elderly based on a literature review. Methods: This study used the literature review method with guidelines from Grove and Gray EBP. Articles were searched through Google Scholar, Ebsco, and Elsevier databases with the keywords "family support," "hypertension," and "elderly." Articles were screened using the PICOS Framework to ensure relevance to the research topic. Results: Analysing 10 articles that met the selection criteria, we found that good family support contributed to improved medication adherence, hypertension diet adherence, and improved quality of life for the elderly. The most influential forms of support include emotional, social, instrumental, and financial support. Conclusion: Family support plays a significant role in the management of blood pressure in hypertensive elderly. Elderly people who get emotional, social, instrumental, and financial support from their families show better blood pressure control and higher quality of life. Families can provide optimal support for the elderly with hypertension by offering emotional, informational, instrumental, and appreciation support to improve adherence to medication and maintain a healthy lifestyle.